Direito à moradia: direito especial de personalidade? - Marcelo de Oliveira Milagres (2009)
Housing is a constant need in human life - in its beginning, the maternal uterus, the nitial shell, unarguably a sweet and warm dwelling; later, the idea of home, our corner of the vorld. Housing represents a fundamental dimension of human life: it is the place human beings ome in contact with themselves and the other. The expression "to feel at home" reveals the comfort and the need of security in an ntimacy space. Home is also the place of life, of its free development. This dissertation has evolved from the difficulty in defining the right to housing and the nechanisms for its accomplishment in urban spaces. Several national and international Law nstitutes are presented and discussed. Considering that the relation of rights of personality is open, with the principle of lignity of human being as its foundation, we defend that among therh there is the right to housing as 1 special right of personality, with private disappropriation as the juridical instrument for itsiccomplishment. Finally, the right to housing has an economic transcendence, a normative autonomy, tvhich goes beyond the known frontiers of the patrimonial subjective right, and cannot be confusedA'ith the possession right, propriety, housing institutes, domicile or other categories of real rights.